Iteron-Binding ORF157 and FtsZ-Like ORF156 Proteins Encoded by pBtoxis Play a Role in Its Replication in Bacillus thuringiensis subsp. israelensis - Tang, Mujin (American Society for Microbiology (ASM), 2007)
We recently identified a minireplicon of pBtoxis from Bacillus thuringiensis subsp. israelensis that contained an operon encoding two novel proteins (ORF156 and ORF157), both of which are required for replication. ORF157 contains a helix-turn-helix motif and shares no homology with known plasmid replication proteins (Rep), and ORF156 contains the signature motif present in FtsZ/tubulin proteins, the latter of which are known to function in cell division and chromosome segregation. Here we show that the minimal sequence composed of four 12-bp imperfect direct repeats (iterons) in the pBtoxis minireplicon was sufficient to replicate a reporter plasmid in B. thuringiensis subsp. israelensis when ORF156 and ORF157 functions were provided in trans. To further investigate the roles of ORF156 and ORF157 in pBtoxis replication, six-histidine-tagged recombinant rORF156 and rORF157 proteins were purified from Escherichia coli and used in electrophoretic mobility shift assays. Our results demonstrated that rORF157, but not rORF156, binds specifically to the pBtoxis iterons, suggesting that ORF157 functions as a Rep protein. Although rORF156 did not bind to the iteron sequence, we showed that it bound to rORF157-DNA complexes. In addition, we showed that rORF156 has GTPase activity characteristic of the FtsZ/tubulin superfamily of proteins. Taken together, these results suggest that the iterons compose the minimal replication origin (ori) of pBtoxis and that ORF157 and ORF156 are involved in the initiation of pBtoxis replication and possibly in the segregation and partitioning of this plasmid to daughter cells.